Architectural modernism and apartheid modernity in South Africa a critical inquiry into the work of architect and urban designer Roelof Uytenbogaardt, 1960-2009 - Murray, Noëleen (African Studies, 2015)
Roelof Sarel Uytenbogaardt who died in 1998 was, and remains, an important and influential figure in the disciplines of architecture and urban design in South Africa. As a prolific practitioner and academic at the University of Cape Town his influence has been far-reaching. Making use of previously unexamined archival material, this study examines - in detail - the extent of this influence. Importantly the thesis seeks to situate Uytenbogaardt’s work in relation to the rise of apartheid and speculates about the persistence of modernism in contemporary spatial practice. Through examining both the conception and reception of Uytenbogaardt’s buildings and urban plans, the work locates modernist approaches to design prevalent in architecture and urban design as products of apartheid modernity. The controversial and contested nature of Uytenbogaardt’s works provides space for critical analysis and this is evident in the uneven reception of his projects. Architects and urban designers revere him as a ‘master’ while pubic sentiment has very often been strongly negative. This is most strikingly evident in the case of the recent proposed destruction of one of Uytenbogaardt’s most controversial works, the Werdmuller Centre. Constructed in the 1970s after forced removals in Cape Town’s suburb of Claremont, since 2007 architects and urban designers have argued passionately for its retention as an example of ‘timeless’ modernist heritage. Through this and other examples, the thesis explores the complexities presented by professional practice in architecture and urban design in the context of designing buildings for designated publics under apartheid. It argues that the work of practitioners and academics such as Uytenbogaardt is intimately linked to the social crisis of apartheid and that the resultant relationship is one of the complex and interrelated crises of modernist design that persist in post-apartheid South Africa.